Comentarios sobre el pueblo vacceo - Rabanal Alonso, Manuel Abilio; Bragado Toranzo, José María (Estudios humanísticos. Geografía, historia y arte, 1989)
Studies on the Pre-Roman people known vacceo have not been revisited since the sixties. The aim of this paper is to revise the sources we have now, archeological and written - Greek and Latin. We conclude: 1.- Their economy was based on agriculture and cattle. 2.- Socially hierarchycal, the tribal links were disappearing. 3.- Traces of urban element gradually appearing.